The Effect of Clostridium butyricum on Gut Microbiota, Immune Response and Intestinal Barrier Function During the Development of Necrotic Enteritis in Chickens - Huang, Ting; Peng, Xin-Yu; Gao, Biao; Wei, Qi-Lin; Xiang, Rong; Yuan, Ming-Gui; Xu, Zhi-Hong (Frontiers in Microbiology, 2019)
Necrotic enteritis (NE) causes huge economic losses to the poultry industry. Probiotics are used as potential alternatives to antibiotics to prevent NE. It is known that Clostridium butyricum can act as a probiotic that can prevent infection. However, whether or not it exerts a beneficial effect on NE in chickens remains elusive. Therefore, we investigated the impact of C. butyricum on immune response and intestinal microbiota during the development of NE in chickens, including experimental stages with basal diets, high-fishmeal-supplementation diets, and Clostridium perfringens challenge. Chickens were divided into two groups from day 1 to day 20: one group had its diet supplemented with C. butyricum supplementation and one did not. At day 20, the chickens were divided into four groups: C. perfringens challenged and unchallenged chickens with and without C. butyricum supplementation. All groups were fed a basal diet for 13 days and thereafter a basal diet with 50% fishmeal from day 14 to 24. Chickens were infected with C. perfringens from day 21 to 23. At days 13, 20 and 24, samples were collected for analysis of the relative expression of immune response and intestinal mucosa barrier-related genes and intestinal microbes. The results show that C. butyricum can inhibit the increase in IL-17A gene expression and the reduction in Claudin-1 gene induced-expression caused by C. perfringens challenge. Moreover, C. butyricum was found to increase the expression of anti-inflammatory IL-10 in infected chickens. Although C. butyricum was found to have a significant beneficial effect on the structure of intestinal bacteria in the basal diet groups and decrease the abundance of C. perfringens in the gut, it did not significantly affect the occurrence of intestinal lesions and did not significantly correct the shift in gut bacterial composition post C. perfringens infection. In conclusion, although C. butyricum promotes the expression of anti-inflammatory and tight junction protein genes and inhibits pro-inflammatory genes in C. perfringens-challenged chickens, it is not adequate to improve the structure of intestinal microbiota in NE chickens. Therefore, more effective schemes of C. butyricum supplementation to prevent and treat NE in chickens need to be identified.